URDU-AN ANALYSIS OF ISLAMIC JURISPRUDENTIAL RULINGS SPECIFIC TO THE AAL OF MUHAMMAD (PBUH) - Nizar Hussain; Najmul Hasan (دی اسکالر, 2016)
It is the one of the most essential aspects for a Muslim to know and learn about that who are the Aal-e-Muhammad (PBUH), what is their importance in Islam and what are the specific commandments related to them. Allah Almighty has honoured them and raised their ranks. As believer, it is part and parcel of our faith and love towards the messenger of Allah to love his Aal. In our salah we ask Allah swt to bless the Aal of our master Muhammad (PBUH) the way He blessed the Aal of his forefather Ibrahim A.S. But do we really know what Aal means? Scholars and jurists have written extensively on these aspects. In this article, we have presented an overview of the position of scholars regarding what is referred to as Aal of Muhammad (PBUH). We have also summarized and pondered over the rulings and injunctions associated with them, such as prohibition to offer Sadaqat, Kafarat, Zakat and Ushar to them as their rank and status is different from others.